Unraveling the hidden connection: Impacted third molar classification and mandibular canal proximity on panoramic radiographs - Kurniati, Novi; Hani, Sabrina Tiara (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This research is aimed to determine the relation between impacted mandibular third molar’s classification and mandibular canal proximity with panoramic radiograph at RSKGM-P FKG UPDM (B). Materials and Methods: This research used an analytical cross-sectional study. The number of samples in this study was 387 lower third molars from 206 digital panoramic radiographs. The samples were then analyzed based on their classification and their relation to the mandibular canal. Results: The result showed in Pell & Gregory classification, the most related to the mandibular canal is class III (65.8%) with p = 0,000 and position B (58.1%) with p = 0,000. Based on the Winter classification, mesioangular angulation is the most related to the mandibular canal (52.9%) with p = 0,015. Based on the Rood & Shehab classification, it was found that the dominant relation A was 65% in class III with p = 0,000, in position B (58.3%) with p = 0,001, and in mesioangular angulation (61.1%) with p = 0,000. Conclusion: This study shows that the less space available in the mandible, the deeper the position of the impacted tooth in the jaw and their angle affects the proximity of the impacted tooth to the mandibular canal and the radiographic sign of the proximity of the impacted mandibular third molar root to the mandibular canal. This illustrates the need to perform a panoramic radiographic examination prior to performing any intervention on the mandibular third molar.